Historical Gendered Institutional Violence: A Research Agenda for Criminologists - Black, Lynsey (Journal of contemporary criminal justice, 2023)
This article considers the phenomenon of historical gendered institutional harm, examining the widespread incarceration of women and girls in Ireland through the decades following independence in 1922. In this period, thousands of women and girls were confined in a network of sites including Magdalene Laundries and Mother and Baby Homes. The article considers the responses to this history, focusing on those fields which concern themselves with matters of “wrongdoing” and “harm,” responses grounded in law and legalism. We explore both the utility and the limits of these approaches before proposing a criminological research agenda which draws on the centrality of the state in the perpetration of gendered violence. Although Ireland has become a by-word as a case of historical institutional abuse internationally, it remains remarkably understudied by criminologists. The article explores how the Irish example can speak to the discipline of criminology by forcing us to reimagine how we conceive of gendered harms and state-perpetrated harms.